Do Santri Still Obey the Kiai? - Ayu Amanda A’isyatul Khumairo’ (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2025)
Amid narratives of Generation Z’s heightened political awareness through internet access, this study examines a specific subset: santri in Islamic boarding schools—Muslim groups with limited access to the internet to engage in online political discourse. They are frequently characterised as merely a traditional group, and prior studies have largely attributed their political choices to the authority of the kiai (pesantren leaders). To revisit this assumption, the study was conducted in two contrasting Islamic boarding school traditions: traditional and modern. It investigates five potential influences on santri voting behaviour in Indonesia’s 2024 Presidential Election: kiai, teachers (ustaz/ustazah), peer groups, political promises, and evaluations of the Joko Widodo–Ma’ruf Amin government. This study, employing mixed methods, reveals that, contrary to previous studies, kiai exert no significant influence. Instead, teachers shape political preferences through classroom discussions, which also enable students to critically evaluate the Jokowi–Ma’ruf government. These findings enhance the diversity within the field of voting behaviour studies in religion communities with limited internet access while challenging assumptions about Generation Z’s short-term political outlook. The findings also extend voting behavior theory in the context of religious communities with restricted internet access.